2013
DOI: 10.3174/ajnr.a3469
|View full text |Cite
|
Sign up to set email alerts
|

CT Density Measurement and H:H Ratio Are Useful in Diagnosing Acute Cerebral Venous Sinus Thrombosis

Abstract: BACKGROUND AND PURPOSE:Brain CT is widely used to exclude or confirm acute cerebral venous sinus thrombosis. The purpose of this study was to assess the value of attenuation measurement and the H:H ratio on unenhanced brain CT scans in the diagnosis of acute cerebral venous sinus thrombosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
79
2
6

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(92 citation statements)
references
References 10 publications
5
79
2
6
Order By: Relevance
“…The concentration of hemoglobin is one of the determining factors as it has a linear correlation with the attenuation while platelets and atheromatous or cellular debris are known to decrease the attenuation of the thrombus on CT [9], [12][14], [34][36]. Studies on this topic, however, are experimental, animal studies, or investigations of the venous sinus thrombus.…”
Section: Discussionmentioning
confidence: 99%
“…The concentration of hemoglobin is one of the determining factors as it has a linear correlation with the attenuation while platelets and atheromatous or cellular debris are known to decrease the attenuation of the thrombus on CT [9], [12][14], [34][36]. Studies on this topic, however, are experimental, animal studies, or investigations of the venous sinus thrombus.…”
Section: Discussionmentioning
confidence: 99%
“…CT‐venography is a decent and less expensive alternative to MRI for the diagnosis of CVT, but it is inferior for the visualization of brain parenchymal lesions . Unenhanced CT is generally insufficient for the diagnosis, although a recent small study reported promising results on the diagnostic accuracy of CT density measurement of the dural sinuses in acute CVT .…”
Section: Clinical Manifestations and Diagnosismentioning
confidence: 99%
“…A positive correlation and significant association have been established between hemoglobin (hematocrit) levels and the attenuation of blood on unenhanced CT images [14,15]. The increase in attenuation (i.e., radiodensity) is caused by clot retraction, as the process of clot retraction includes the elimination of water, which increases the concentration of red blood cells and hemoglobin [16]. Based on the autopsy findings, the high attenuation areas in the present cases' digestive tracts corresponded to the location of the clotting.…”
Section: Discussionmentioning
confidence: 98%